IBD-Associated Atg16L1T300A Polymorphism Regulates Commensal Microbiota of the Intestine - Liu, Hongtao; Gao, Ping; Jia, Baoqian; Lu, Na; Zhu, Baoli; Zhang, Fuping (Frontiers in Immunology, 2022)
The development of inflammatory bowel disease (IBD) is driven by the interaction among host genetics, microbiota, and the immune system of the entire digestive tract. Atg16L1T300A polymorphism is a genetic factor that confers increased risk for the pathogenesis of Crohn's disease. However, the exact contributions of Atg16L1T300A to intestinal mucosal homeostasis are not well understood. Here we show that Atg16L1T300A polymorphism impacts commensal bacterial flora in the intestine under steady-state. Analysis of intestinal bacteria from Atg16L1T300A/T300A mice showed that they harbored an altered microbiota in both terminal ileum and colon compared to co-housed WT mice. Interestingly, Atg16L1T300A/T300A mice harbored a significant increase in the abundance of Tyzzerella, Mucispirillum, Ruminococcaceae, and Cyanobacteria that was known associated with IBD. Moreover, Akkermansia, a bacterial that is mucin-associated, was reduced greatly in Atg16L1T300A/T300A mice. Further analysis indicated that Goblet cells of Atg16L1T300A/T300A mice had diminished mucin secretion that resulted from defective autophagy. Finally, Atg16L1T300A/T300A mice developed more severe inflammation in DSS colitis model than WT mice. These results indicate that the altered microbiota in Atg16L1T300A/T300A mice might be an important factor that contributed to the risk of Atg16L1 T300A carriers to Crohn's disease and supports a multi-hit disease model involving specific gene-microbe interactions.